The role of social media in attitudinal loyalty creation - Doan, Thi (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku. Turku School of Economics|, 2017)
This study discusses the important role of social media to the creation of attitudinal loyalty. The purpose of the study is to build a framework which illustrates the complex connections among the social media’s functional elements and attitudinal loyalty’s constructs in order to explain how social media make impacts on different phases and levels of attitudinal loyalty formation process. Conceptual meta-framework building methodology is employed in this study with multiple theories in marketing and consumer behavior disciplines being investigated, redesigned and integrated. Without empirical analysis, the body of the study is built completely based on an extensive literature review. This literature investigation is constructed using a wide range of materials in varied formats such as books, journals, conference reports and online articles from reliable sources. The study finds that by utilizing the major functions of social networking sites, companies can affect consumers’ attitudinal loyalty creation process at many levels, from raising brand awareness to enhancing brand meaning then growing cognitive loyalty and emotional attachments in consumers. Also, social media enables companies to not only build strong relationship with existing followers but also establish positive associations in potential customers through electronic word-of-mouth effect. The findings of this study contribute to enrich the understanding of the relationship between social media and attitudinal dimension of customer loyalty. Nevertheless, future research is necessary in order to test the usefulness of the proposed meta-framework in general business reality and fully understand the applicability of the framework in different contextual backgrounds.